2018
DOI: 10.1111/1440-1630.12492
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers to aligning rehabilitation goals to patient life roles following acquired brain injury

Abstract: Goal setting in alignment with life roles is important in acquired brain injury rehabilitation, but may be limited. This process can be enhanced by including patients and their significant others in early goal setting conversations, along with regular goal review across the rehabilitation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Like every provider who treats patients with TBI, the VCP will often need to refer patients to members of the TBI-treatment team who might not already have been recruited and to facilitate communication of rehabilitative plans. The value of including a patient's significant social supporters in these conversations cannot be overstated [124].…”
Section: The Post-examination Conversationmentioning
confidence: 99%
“…Like every provider who treats patients with TBI, the VCP will often need to refer patients to members of the TBI-treatment team who might not already have been recruited and to facilitate communication of rehabilitative plans. The value of including a patient's significant social supporters in these conversations cannot be overstated [124].…”
Section: The Post-examination Conversationmentioning
confidence: 99%
“…Repeated PAM clustering using the second proximity matrix to generate the new classes. 6. We then calculated the CVIs with the cluster.stats function of the fpc R package.…”
Section: Combined Cluster Analysis Approaches: Unsupervised Random Fomentioning
confidence: 99%
“…Patients with TBI can show various combinations of motor, cognitive, behavioral, psychosocial, and environmental issues that have a huge impact on everyday activities [5], and these issues can greatly interfere with the effectiveness of rehabilitation interventions. It has been proposed that the efficacy of the rehabilitation would increase if programs moved from disease-centered to person-centered issues such that the rehabilitation is tailored to individual needs [6,7]. A number of studies have suggested that brain injury does not have any prototypical pattern of cognitive performance and outcome but may be best characterized by heterogeneity, both in regard to cognitive deficit and ultimate level of functioning [8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed these patients can show various combinations of clinical, cognitive, behavioral, psychosocial, and environmental issues (2), which can interfere with the effectiveness of rehabilitation interventions. It has been proposed that the efficacy of rehabilitation should increase if programs would move from disease-centered to person-centered, tailored on the needs of every single individual (3, 4). In this way, it would be simpler to target routines, occupations, and relationships more effectively (5).…”
Section: Introductionmentioning
confidence: 99%